Immediate Effect of Neuromuscular Electrical Stimulation on Swallowing in Elderly People with Alzheimer's Dementia - Ribeiro, Eliene Giovanna; Oliveira, Cris Magna dos Santos; Mourão, Aline Mansueto; Vicente, Laélia Cristina Caseiro; Motta, Andréa Rodrigues; Honório, Heitor Marques; Berretin-Felix, Giédre (International Archives of Otorhinolaryngology, 2025)
Dysphagia affects a significant number of patients with Alzheimer's dementia. Neuromuscular electrical stimulation may be a promising resource for dysphagia rehabilitation in this population.To investigate the immediate effects of neuromuscular electrical stimulation on hyoid bone displacement, pharyngeal transit time, and swallowing safety in elderly people with Alzheimer's dementia.We evaluated 30 elderly individuals with an average age of 82.79 years, regardless of the stage of dementia and with reduced hyolaryngeal elevation, using the Northwestern Dysphagia Patient Check Sheet. Neuromuscular electrical stimulation was performed at the sensory and motor levels in the submental region during videofluoroscopy, with food being offered in solid, pudding, and liquid consistencies, and in portions of 5 mL and 10 mL. We applied Analysis of variance and the Friedman test, adopting a significance level of < 5%.The comparison between the sensory and motor levels of stimulation showed that there was a significant difference in hyoid bone displacement for the mushy consistency, with neuromuscular stimulation at the motor level. There was no difference in the application of stimuli for the other consistencies regarding hyoid bone displacement, pharyngeal transit time, and the penetration and aspiration scale.In elderly people with Alzheimer's dementia, neuromuscular electrical stimulation at the motor level generated a reduction in hyoid bone displacement during swallowing of food with pudding consistency, with no effects on pharyngeal transit time or swallowing safety.
Keywords: dementia; Alzheimer disease; deglutition disorders; electrical stimulation; speech-language pathology